PUBLIC SPEAKING ACTIVITIES TO IMPROVE STUDENTS’ SPEAKING SKILLS - Muhajir, R.; Sri Redjeki, Indah (ENGLISH JOURNAL, 2018)
In this region, English is mostly learned as the main subject. It starts from elementary school to university level, but most high school graduates cannot speak English even though they have been studying it for three years or more. This stimulated the researcher to create a breakthrough that would make it easier for students to practice their speaking skills as much as possible. The programs consisted of three activities: discussion (hot issues talk), debate forum, and speech presentation. Participants in this study were 50 second-year high school students in Indonesia. They were divided into two groups: experimental and control classes. The experimental class consisted of 25 students who engaged in public speaking activities, while the control class consisted of 25 students who did not participate. The findings of this quantitative analysis showed that members of the experimental class who engaged in public speaking exercises experienced an increase in their English-speaking skills. It can be discovered that public speaking activities can be used as an approach to enhancing the ability of high school students to speak.